A Comparative Analysis of the Microbiome of Kiwifruit at Harvest Under Open-Field and Rain-Shelter Cultivation Systems - Sui, Yuan; Zhao, Qianhua; Wang, Zhenshuo; Liu, Jia; Jiang, Mingguo; Yue, Junyang; Lan, Jianbin; Liu, Jing; Liao, Qinhong; Wang, Qi; Yang, Qiya; Zhang, Hongyin (Frontiers in Microbiology, 2021)
The composition of microbial communities can directly affect fruit quality, health status, and storability. The present study characterized the epiphytes and endophytes of ‘Hongyang’ and ‘Cuiyu’ kiwifruit at harvest under grown under open-field (OF) and rain-shelter (RS) cultivation systems. Disease incidence in kiwifruit was significantly lower (p<0.05) under the RS system than it was under the OF system. High-throughput sequencing [16S V3-V4 ribosomal region and the fungal internal transcribed spacer (ITS2)] was conducted to compare the composition of the epiphytic and endophytic microbial community of kiwifruit under the two cultivation systems. Results indicated that the abundance of Actinobacteria, Bacteroidetes, Enterobacteriales, Acetobacterales, Sphingomonas, Pseudomonas, and Sphingobacterium was higher under the RS system, relative to the OF system, while the abundance of Capnodiales, Hypocreales, Vishniacozyma, and Plectosphaerella was also higher under the RS system. Some of these bacterial and fungal taxa have been reported to as act as biocontrol agents and reduce disease incidence. Notably, the α-diversity of the epiphytic bacterial and fungal communities on kiwifruit was higher under RS cultivation. In summary, RS cultivation reduced natural disease incidence in kiwifruit, which may be partially attributed to differences in the structure and composition of the microbial community present in and on kiwifruit.